THE MOTIF OF THE BLIZZARD-FATE IN THE WORKS OF A.S. PUSHKIN - Goncharova Nina Vasilevna (Web of Journals Publishing, 2025)
The article examines one of the interesting topics of Russian literature – the theme of fate. The image of the blizzard-fate is not just a plot element, but a deep philosophical symbol that raises questions about the relationship between man and the elements, free will and forces beyond our control, justice and tragic inevitability.
Keywords: theme of fate, motif of a blizzard, demonic origin, inner enlightenment, Russian roulette.